2016
DOI: 10.1136/openhrt-2016-000510
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mortality trends due to cardiovascular diseases in Panama, 2001–2014

Abstract: ObjectiveCardiovascular diseases (CVDs) are still the leading cause of death worldwide despite the recent decline in mortality rates attributable to CVD in Western Europe and the Americas. The aim of this study is to investigate mortality trends due to ischaemic heart disease (IHD) and stroke in Panama from 2001 to 2014, as well as the mortality differences by sex and age groups.MethodsData were obtained from the National Mortality Register. The International Classification of Diseases 10th revision codes (ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In addition, these differences have been largely theorized to be due to stage of epidemiologic transition of the countries ( Figure 4 ). 9 , 22 , 23 , 24 , 25 Epidemiologic transition is the process by which countries “advance” through stages on the basis of the types of diseases most affecting their population. 22 , 23 The transition is broken down into 4 stages: pestilence and famine, receding pandemics, degenerative and man-made diseases, and delayed degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these differences have been largely theorized to be due to stage of epidemiologic transition of the countries ( Figure 4 ). 9 , 22 , 23 , 24 , 25 Epidemiologic transition is the process by which countries “advance” through stages on the basis of the types of diseases most affecting their population. 22 , 23 The transition is broken down into 4 stages: pestilence and famine, receding pandemics, degenerative and man-made diseases, and delayed degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 24 This observation should be interpreted with caution as cardiovascular disease has been the focus of research and funding for a longer period than cancer has, and through preventive and life-prolonging interventions created during the last 20 years, we have seen a decline in age-standardized cardiovascular disease–related deaths. 8 , 9 , 10 , 24 , 25 , 26 A study by Carrión Donderis et al 24 in 2016 in Panama, a high-income country, found similar results of reduced cardiovascular disease mortality due to improved treatment, lower tobacco consumption, and reduction of comorbidities. Within cancer research, there have been notably fewer curative developments for the most advanced cancers and the cancer types that contribute the most to mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that there was a decrease in mortality rates in IHD and stroke during the study period. Similarly, a recent study reported a decline in the trend of stroke mortality from 2001 to 2014 and a decrease in IHD mortality that started in 2010 [10]. Whether the decrease in trends occurred similarly in provinces and regions is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest estimates, indigenous peoples represent 12% of the total population in the country [9]. CVD mortality trends have declined in recent years [10], yet CVD is still the leading cause of death, responsible for 28% of national mortality [11].…”
Section: Introductionmentioning
confidence: 99%